2017 14th International Computer Conference on Wavelet Active Media Technology and Information Processing (ICCWAMTIP) 2017
DOI: 10.1109/iccwamtip.2017.8301509
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing the collective learning effects in regional economic development

Abstract: Collective learning in economic development has been revealed by recent empirical studies, however, investigations on how to benefit most from its effects remain still lacking. In this paper, we explore the maximization of the collective learning effects using a simple propagation model to study the diversification of industries on real networks built on Brazilian labor data. For the inter-regional learning, we find an optimal strategy that makes a balance between core and periphery industries in the initial a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…The importance of knowledge diffusion in the diversification of economic activities, however, is not limited only to the export of products. It has also been observed in the development of regional industries (Neffke et al, 2011;Gao et al, 2017), research activities (Guevara et al, 2016), and technologies (Kogler et al, 2013;Boschma et al, 2014), suggesting that relatedness between economic activities facilitates knowledge diffusion in general, not only in the context of international trade.…”
Section: Introductionmentioning
confidence: 98%
“…The importance of knowledge diffusion in the diversification of economic activities, however, is not limited only to the export of products. It has also been observed in the development of regional industries (Neffke et al, 2011;Gao et al, 2017), research activities (Guevara et al, 2016), and technologies (Kogler et al, 2013;Boschma et al, 2014), suggesting that relatedness between economic activities facilitates knowledge diffusion in general, not only in the context of international trade.…”
Section: Introductionmentioning
confidence: 98%
“…Social reinforcement effects also occur widely in other types of behavioral adoption processes, such as using menstrual cups [150], adopting seeding strategies [151], taking a new diagnostic method [152], joining social movement activities [153], retweeting politics hashtags [154], and learning a new industry [155].…”
Section: Social Reinforcementmentioning
confidence: 99%
“…Using 25 years of economic data in China between 1990 and 2015, they addressed the endogeneity concerns by using the difference-in-differences analysis. Results showed that the high-speed rail development increased the industrial similarity of connected pairs of neighboring provinces 45 .…”
Section: Introductionmentioning
confidence: 99%
“…The reduction was largely driven by the concurrent drop in fixed asset investments of those bypassed counties 44 . Gao et al 45 introduced the concept of inter-industry and inter-regional learnings of regional economic development. Using 25 years of economic data in China between 1990 and 2015, they addressed the endogeneity concerns by using the difference-in-differences analysis.…”
Section: Introductionmentioning
confidence: 99%